Organization and Reporting of Public Financial Accounts: Insights and Policy Implications from the Singapore Budget. Issue 4 (25th October 2016) - Kwan, Chang Yee; Bali, Azad Singh; Asher, Mukul G.
Abstract : This paper analyses the Singapore government budget's organization and reporting structure, and draws lessons and policy implications for improving public financial management practices. The paper finds that Singapore's fiscal marksmanship record has been poor with consistent underestimates of revenue and overestimates of expenditure. Second, subtle divergences from international reporting standards limit the information available and constrain the budget's analytical usefulness in international comparisons. Third, current reporting conventions of the budget fail to provide an adequate representation of the government's fiscal position. Fourth, revised estimates of budgetary balances in line with international reporting standards show a considerable increase in the fiscal space available. The policy implications of these findings are discussed, as well as some reporting changes which can help improve the fiscal marksmanship record, increase public sector transparency and accountability, and facilitate better quality discourse among all stakeholders on public financial management. Abstract : This paper examines the organization and reporting of the Singapore budget. The analysis finds a poor fiscal marksmanship record, divergences from international reporting standards and understatement of the fiscal space available. Potential socio‐economic impacts of the budget's reporting are discussed with suggestions to improve its information quality for policy discourse.